Hubungan antara Stromal Tumor Infiltrating Lymphocytes (TIL) dengan ekspresi Programmed Death-Ligand 1 (PD-L1) pada karsinoma payudara invasif tipe tidak spesifik subtipe Human Epidermal Growth Factor Receptor-2 (HER-2) enriched di RSUP Sanglah, Bali, Ind - Popi Imelda Margareth Sitompul; Herman Saputra; Luh Putu Iin Indrayani Maker; I Gusti Ayu Sri Mahendra Dewi; Ni Putu Sriwidyani; I Made Muliarta (Intisari Sains Medis, 2021)
Background: Breast cancer is the most common malignancy cancer in women. This malignancy is molecularly heterogeneous, where overexpression of the HER-2 growth factor receptor generally has a more aggressive nature. The role of immune system interaction, namely Tumor Infiltrating Lymphocytes (TIL) and Programmed Death-Ligand 1 (PD-L1) expression, is associated with prognostic and predictive factors. Therefore, this study aims to investigate the association between stromal TIL with PD-L1 expression in invasive breast carcinoma non-specific type HER-2 enriched subtype.Methods: This study was an observational analytical study with cross-sectional design from January 1st 2015 to December 31st 2019. The samples were taken from a paraffin block of patients with invasive breast carcinoma non-specific type, that has performed histopathological examination, ER, PR, HER-2 and FISH/CISH immunohistochemistry examination at the Anatomical Pathology Laboratory of Sanglah Hospital Denpasar. The samples obtained were stained with PD-L1 immunohistochemistry. The preparation was evaluated to assess TIL. Data were analyzed using SPSS version 20 for Windows.Results: The study found a statistically significant association between stromal TIL with PD-L1 expression in tumor cells (p = 0.018).  There is statistically significant association between stromal TIL with PD-L1 expression in TIL (p = 0.001). There is statistically significant association between stromal TIL with PD-L1 expression in total tumor cells and TIL (p = 0.007) in invasive breast carcinoma non-specific type HER-2 enriched subtype at Sanglah Hospital, Denpasar.Conclusion: In conclusion, there is an association between stromal TIL with the expression of PD-L1 in tumor cells and TIL in invasive breast carcinoma non-specific type HER-2 enriched subtype.  Latar Belakang: Kanker payudara merupakan keganasan tersering pada wanita. Keganasan ini bersifat  heterogen ditinjau dari aspek molekuler, dimana overekspresi HER-2 umumnya memiliki sifat yang lebih agresif. Peranan sistem imun, yakni ekspresi Tumor Infiltrating Lymphocytes (TIL) dan Programmed Death-Ligand 1 (PDL-1) dihubungkan dengan faktor prognostik. Oleh karena itu, penelitian ini bertujuan untuk mengevaluasi hubungan antara stromal TIL dengan ekspresi PD-L1 pada karsinoma payudara invasif tipe tidak spesifik subtipe HER-2 enriched.Metode: Penelitian ini merupakan penelitian observasional analitik dengan rancangan studi potong lintang mulai dari 1 Januari 2015 sampai 31 Desember 2019. Sampel adalah blok parafin penderita karsinoma payudara invasif tipe tidak spesifik yang telah dilakukan pemeriksaan histopatologi, imunohistokimia ER, PR, HER-2 dan FISH/CISH  di Laboratorium Patologi Anatomi RSUP Sanglah Denpasar. Sampel yang diperoleh dilakukan pulasan imunohistokimia PD-L1 Preparat sampel digunakan untuk menilai TIL. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Pada penelitian ditemukan hubungan yang signifikan secara statistik antara stromal TIL dengan ekspresi PD-L1 pada sel tumor (p=0,018). Terdapat hubungan yang signifikan secara statistik  antara stromal TIL dengan ekspresi PD-L1 pada TIL (p=0,001). Terdapat hubungan yang signifikan secara statistik antara stromal TIL dengan ekspresi PD-L1 pada total sel tumor dan TIL (p=0,007) pada karsinoma payudara invasif tipe tidak spesifik subtipe HER-2 enriched di RSUP Sanglah Denpasar.Kesimpulan: Hasil penelitian ini menunjukkan terdapat hubungan bermakna antara stromal TIL dengan ekspresi PD-L1 sel tumor dan TIL pada karsinoma payudara invasif tipe tidak spesifik subtipe HER-2 enriched.